Factors Influencing Employee Engagement and Performance: Examination of Transformational Leadership and Empowerment - Maulia, Indah Rizki; Ali, Hapzi (Dinasti Publisher, 2024)
This study aims to build a hypothesis for further research, namely to formulate: a) impact from transformational leadership to employee engagement; b) impact from transformational leadership to employee performance; c) impact from empowerment to employee engagement; d) impact from empowerment to employee performance; e) impact from employee engagement to employee performance. The research method used is literature review by studying previous research which examine the impact of transformational leadership, empowerment on employee engagement and performance. From this systematic literature review study, it is concluded that hypotheses can be formulated for further research are: a) H1: there is positive impact from transformational leadership to employee engagement; b) H2: there is positive impact from transformational leadership to employee performance; c) H3: there is positive impact from empowerment to employee engagement; d) H4: there is positive impact from empowerment to employee performance; e) H5: there is positive impact from employee engagement to employee performance.